Molecular steps of G-overhang generation at human telomeres and its function in chromosome end protection - Dai, Xueyu (Nature Publishing Group, 2010)
Telomeric G-overhangs are required for the formation of the protective telomere structure and telomerase action. However, the mechanism controlling G-overhang generation at human telomeres is poorly understood. Here, we show that G-overhangs can undergo cell cycle-regulated changes independent of telomerase activity. G-overhangs at lagging telomeres are lengthened in S phase and then shortened in late S/G2 because of C-strand fill-in, whereas the sizes of G-overhangs at leading telomeres remain stable throughout S phase and are lengthened in G2/M. The final nucleotides at measurable C-strands are precisely defined throughout the cell cycle, indicating that C-strand resection is strictly regulated. We demonstrate that C-strand fill-in is mediated by DNA polymerase α (polα) and controlled by cyclin-dependent kinase 1 (CDK1). Inhibition of CDK1 leads to accumulation of lengthened G-overhangs and induces telomeric DNA damage response. Furthermore, depletion of hStn1 results in elongation of G-overhangs and an increase in telomeric DNA damage. Our results suggest that G-overhang generation at human telomeres is regulated by multiple tightly controlled processes and C-strand fill-in is under the control of polα and CDK1.